A reclamação constitucional - Ribeiro, Rafael Vieira (2018)
The constitutional complaint is an institute of legal nature of embedded action of the intention to carry out the constitutionality control in Brazil. With the advent of the new Civil Procedure Code (NCPC) in 2015, its use began to encompass the decisions of state civil recursion classes throughout the country. The purpose of this study is to present the history of the complaint, its legal evolution as well as its applications according to the NCPC in order to promote the discussion about its advances and to detail its importance in the current Brazilian scenario. For its accomplishment a literature review was carried out that covered the publications available in the portals of legal knowledge, the works of the main theorists of the subject as well as the legal apparatus that deals with it, as the law and the precedents. It was possible to verify the evolution of the legislation in relation to the complaint, showing the concern of the legislator to consult civil society for its construct, innovating in the scope, which was previously limited to the higher courts. The compatibility of the new complaint system with the Federal Constitution has been questioned, in particular by the arguments that have hammered out the binding precedent created by the EC in 45/2004 and, mainly, by its normative forecast to be infraconstitutional in nature. Nevertheless, it is perceived that, instead of offending any provision of the Federal Constitution of 1988, the new complaint, in particular to guarantee the authority of the jurisprudential understanding of any court, asserts the right to equality, to guarantee legal certainty and reasonable length of time.